Representasi Sejarah Dalam Novel Kidung Anjampiani Karya Bre Redana Serta Penyusunannya Sebagai Bahan Ajar Dalam Materi Teks Narasi Kelas XII SMA - Albait, Asifa Nurzia; Hartati, Dian; Meliasanti, Ferina (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to (1) depict the historical representations in the novel "Kidung Anjampiani" by Bre Redana, and (2) develop teaching materials for narrative texts for senior high school (SMA) twelfth-grade students. The subject of this study is the novel "Kidung Anjampiani" by Bre Redana, and the research object includes the historical representations in the novel using Swingewood's sociological literary theory, and the development of teaching materials for narrative texts for twelfth-grade SMA. This research employs a qualitative approach with a descriptive-analytical method. The techniques used include literature review and note-taking. The results of the study reveal three aspects of historical representation, namely: (1) objective depictions of human life in society, including human relationships with religion and beliefs that correspond to historical facts of the Majapahit era. Hinduism and Taoism in the novel represent the religions and beliefs of Majapahit society. Political conflicts generating tension demonstrate alignment with Majapahit history, and instances of rebellion correspond to historical events documented in various texts. The political system used by Majapahit in the novel is consistent with the hereditary and kinship system, and the social strata depicted in the novel, including the Brahmana, Kshatriya, Sudra, and Vaishya, represent the caste divisions of the Majapahit era. (2) Social processes underlying human existence in society include cultural patterns marked by the presence of mourning traditions, beliefs in myths and folklore, artistic expressions indicated by kakawin, economic activities reflecting livelihood pursuits such as trade, agriculture, ports, and fishing. Additionally, language development as a tool for societal interaction is marked by the use of the Javanese language in various expressions. The research findings are then utilized in developing teaching materials in the form of an e-module for the twelfth-grade SMA narrative text curriculum.